Analisis keseragaman kolektor surya pelat datar glazed dan unglazed - Efendi, Rustam; Nelwan, Leopold Oscar; Wulandani, Dyah (Jurnal Teknik Mesin Indonesia, 2024)
Solar collectors, as a means of converting solar energy into thermal energy, are the focus of this study. Two types of solar collectors used, namely glazed flat plates (KSPDG) and unglazed flat plates (KSPDU), are tested to evaluate uniformity of performance. The study was conducted using a testing setup that included a tank, water pump, thermocouple, flowmeter, anemometer, and pyranometer. Uniformity testing is performed by analyzing inlet temperature, outlet temperature, ambient temperature, and solar irradiation during 8 hours of testing. Test results show that both types of solar collectors show similar trends in performance, with increases in water temperature aligned with increased solar irradiation. Statistical analysis shows a similar level of uniformity between KSPDU I and KSPDU II, as well as between KSPDG I, KSPDG II, and KSPDG III.